PERLINDUNGAN POTRET UNTUK PROMOSI TANPA IZIN PIHAK TERKAIT BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 - Nurtati Dwika; Emmi Siregar; Irda Pratiwi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2020)
portrait are photography work with humans objects. And the portrait it self is regulated by copyright law. If a portrait is taken without the consent of the photographed, the photografer will be subject to law number 28 of 2014. if the portrait is used for promotion or published without the must permission of the photographer or the heir, the photografer must first ask permission of the photografer. If the photographer does not have permission to the photographed or the heirs to carry out commercial uses, procurement, distribution, etc., will be subject to article 115 of law number 28 of 2014 concerning copyright. The photographer will be charged with a maximum fine of Rp 500.000.000,00 (five hundred million rupiah). It would be better if a photographer who would take someone’s portrait for promotion would be better to ask permission of the portrait or ask permission from the heirs first